Treatment satisfaction in Chinese medicine outpatient care: a comparison of patients’ and doctors’ views - Zhang, Yanhong (BMC Complement Altern Med, 2019)
BACKGROUND: Both doctors’ and patients’ opinions are important in the process of treatment and healthcare of Chinese medicine. This study is to compare patients’ and doctors’ treatment satisfaction over the course of two visits in a Chinese medicine outpatient setting, and to explain their respective views. METHODS: Patients’ chief complaints were collected prior to the outpatient encounter. The doctor was then asked (through a questionnaire) to state what complaints he or she was prioritizing during the process of diagnosing disease and making a prescription for herbal medicine or acupuncture treatment. On the next visit, both the patient and the doctor completed a questionnaire assessing satisfaction with the treatment of Chinese medicine prescribed in the first visit and administered by the patient at home. A 5-point Likert scales was used to assess the patients’ and doctors’ satisfaction with treatment. The timing of the follow-up appointment was determined by the doctor. One chief specialist, one associate chief specialist and one attending practitioner in Chinese medicine, and 60 patients having a follow-up appointment with one of the doctors, participated in the study. RESULTS: For 11 patients, their most urgent complaint was different from what the doctor’s choose to focus on in his or her treatment. And only one patient refused to comply due to his or her dissatisfaction with the treatment focus of the doctor. Overall, 59 patients completed the satisfaction assessment, and 53 patients visited their doctors for a follow-up appointment. Patients’ total satisfaction was higher than their doctors’ (mean 3.55 vs. 3.45), and correlation of patients’ and doctors’ treatment satisfaction was moderate (r = 0.63, P < 0.01). Both of the patients’ and doctors’ satisfaction ratings were correlated with treatment adherence (P < 0.001). The predictors of their treatment satisfaction were different. Doctors’ satisfaction with treatment was a significant factor in the process of making further clinical decisions. CONCLUSION: Patients and doctors form their opinion about the treatment effects in different ways. When evaluating treatment satisfaction, doctor’s opinions are also an important indicator of positive or negative clinical effects and affect the subsequent decisions-making.